A computational study on the aerodynamics of a twin-box bridge with a focus on the spanwise features. Issue 209 (February 2021) - Álvarez, A.J.; Nieto, F.; Kwok, K.C.S.; Hernández, S.
Abstract: The wind flow around twin-box decks is particularly complex due to the very important role played by the slot distance between girders and the presence of the downwind box that is immersed in the wake of the upwind box. Detailed experimental studies on the three-dimensional flow features of this deck typology are certainly challenging, and CFD simulations have not tackled this problem so far. The goal of this 3D LES piece of research is to shed some light on the complex flow features around twin-box decks, particularly when the deck geometry is fully three-dimensional due to the presence of the transversal beams linking together the deck girders. Integral parameters, mean and instantaneous flow structures and spanwise correlations are studied for a segment of the Stonecutters Bridge. It has been found that the presence of the transversal beam plays a key role in the flow correlation loss, identifying, for instance, the out-of-phase shedding of vortices at different sides of the transversal beam. The numerical results agree well with experimental data in the literature, and offer a richer and more comprehensive explanation for the identified aerodynamic responses. Highlights: 3D LES simulations are used to study the aerodynamics of twin-box decks. Two arrangements are considered: with and without transversal beams linking the box girders. Integral parameters, pressure and friction coefficient distributions are studied. Spanwise correlations are adopted to analyse three-dimensional ow features. The transversal beams play a key role in the aerodynamic response.